Legality and Safety Regulations of Electric Vehicle Batteries in Indonesia: Challenges and Implementation of National Standards - Maria Natasha Rudijanto; Amad Sudiro (Dinasti Research, 2025)
This study examines the legality and safety regulatory aspects related to the use of electric vehicle batteries in Indonesia, especially focusing on the risk of fire due to the failure of lithium-ion batteries which are often used as the main energy source. With the increasing adoption of electric vehicles, Indonesia is faced with the challenge of setting safety standards that are able to keep up with the development of battery technology and meet consumer expectations and international standards. In this study, an analysis of government policies, harmonization of international regulations, and the importance of battery testing as a risk mitigation measure was carried out. Battery testing is a vital component to ensure the safety and reliability of electric vehicles, involving procedures such as thermal resistance tests, short-circuit protection, and mechanical integrity testing. By applying normative juridical methods through conceptual approaches, laws and regulations, and international case studies, this study aims to provide recommendations for improvement of battery safety regulations and procedures in Indonesia to support the creation of a safer and more sustainable transportation environment.